2017
DOI: 10.1177/1758573217736008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obesity on fatty infiltration of the rotator cuff musculature in patients without rotator cuff tears

Abstract: Background: The modified Goutallier classification system describes the fatty infiltration of rotator cuff musculature (RCM) seen on magnetic resonance imaging (MRI) to assist with surgical decision-making for patients with rotator cuff tears (RCT). We describe the relationship between body mass index (BMI) and fatty infiltration in patients without RCT. Methods: Twenty-five patients from each of four different BMI ranges (< 25 kg/m 2 ; 25 kg/m 2 to 30 kg/m 2 ; 30 kg/m 2 to 35 kg/m 2 ; > 35 kg/m 2) were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…14 On the other hand, it has recently been suggested that hyperlipidemia alone may not be a risk factor for retear after rotator cuff surgery. 3,23 In the present study, similar to Ishitani et al, 17 no association was found between Goutallier classification, hyperlipidemia, or tear size and stump classification. In our opinion, stump classification is an assessment of rotator cuff tendon quality, and excessive traction on a degenerated rotator cuff due to fatty degeneration may lead to retear.…”
Section: Discussionsupporting
confidence: 87%
“…14 On the other hand, it has recently been suggested that hyperlipidemia alone may not be a risk factor for retear after rotator cuff surgery. 3,23 In the present study, similar to Ishitani et al, 17 no association was found between Goutallier classification, hyperlipidemia, or tear size and stump classification. In our opinion, stump classification is an assessment of rotator cuff tendon quality, and excessive traction on a degenerated rotator cuff due to fatty degeneration may lead to retear.…”
Section: Discussionsupporting
confidence: 87%
“…FI, in particular, is a limiting factor that may preclude the option to proceed with repair . In the setting of more global disturbances of muscle structure such the muscular dystrophies or in association with widespread hormonal imbalances such as obesity and diabetes, other muscles can also develop FI . In the case of musculotendinous injuries that orthopedic surgeons more often encounter, the RC has been shown to preferentially develop FI, which suggests there may be intrinsic differences across muscle groups that results in the RC being predisposed to FI .…”
Section: Discussionmentioning
confidence: 99%
“…Although FI is common in RC tears, this pattern of pathology is not ubiquitous across all types of musculotendinous injuries at all anatomic locations, with the exception of some genetic condition, such as muscular dystrophies, and more global metabolic disturbances such as obesity and type 2 diabetes . Multiple studies have observed high degrees of FI in paraspinal muscles in patients with congenital and degenerative spine diseases .…”
mentioning
confidence: 99%
“…24 Hyperlipidemia is a recognized risk factor for degenerative rotator cuff tear 1,27 and fatty infiltration of rotator cuff muscles. 30 Deposition of lipid as oxidized low-density lipoprotein forms tendon xanthoma, 24 resulting in altered mechanical properties, chronic inflammation, and impaired circulation, contributing to the pathogenesis of rotator cuff tear and subsequent poor tendon-bone healing after repair. 5,9,28,40 In animal models replicating hyperlipidemia, a greater incidence of poor healing or retear 5,10,14,28 has been reported along with progression of fatty infiltration of the rotator cuff muscles following surgical repair.…”
Section: Level Of Evidencementioning
confidence: 99%